Motivating Course Completion in Executive Development - Foster, David (International Journal of Advanced Corporate Learning (iJAC), 2015)
An innovative online approach to executive development is described. The approach utilizes asynchronous and synchronous elements, required submission of assignments, and other features resembling those of online college courses. Design of the learning experience, though, has been observant of the various motivations of busy executives. The approach so far has resulted in high rates of course completion.